Comparative study of intraocular pressure variation among healthy and diabetic individuals - Afreen Saif; Narsingh Verma; Shraddha Singh; Sushma S. Rapelly; Deep Shikha (Journal of Family Medicine and Primary Care)
Background: Diabetes and glaucoma share several common risk factors and pathophysiological similarities. Elevated intraocular pressure, a key pathogenic feature of glaucoma and its progression, has been found to be influenced in diabetic patients. Furthermore, a link between poor glycemic control and increased intraocular pressure has been documented. Given the rising prevalence of diabetes mellitus and its emergence as a new pandemic with widespread effects, it is crucial to thoroughly study its impact on various body systems and implement measures to reduce these adverse effects. Therefore, this study aims to investigate the variation in intraocular pressure and its relationship with different pathogenic risk factors in diabetes mellitus patients to develop effective prevention strategies. Aim: To study the variation in intraocular pressure among the subjects with Type II Diabetes Mellitus Settings and Study Design: This analytical cross-sectional study conducted at KGMU, Ophthalmology OPD. Methods and Materials: Study has been conducted on a total of 140 participants, comprising of 70 Type II DM cases and 70 age, gender-matched controls in 1year duration. Type II DM was confirmed by diagnosis while controls were selected to match in age & gender without diabetes. IOP measurement was done using non-contact tonometry and central corneal thickness was measured by non-contact method using NIDEK CEM-530 specular microscope. Regression analysis was used to assess association between Type II DM and IOP variation. Statistical analysis of the data was done using IBM SPSS Stats 25.0 version with Student t-test, Chi-square test, ANOVA, and Pearson’s correlation with 95% CI is used. P <0.05 is considered significant. Result: Significant distinction in IOP between the between cases and control group is observed. And, also more the duration of diabetes with poor glycemic control may lead to raised IOP. Conclusion: The study rules out the risk factors for raised IOP in general & diabetic population. Thus, emphasizing the need for meticulous ocular care in diabetic individuals.